2020
DOI: 10.1101/2020.09.07.20189688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 transmission in a university setting: a rapid review of modelling studies

Abstract: Managing COVID−19 within a university setting presents unique challenges. At the start of term, students arrive from geographically diverse locations and potentially have higher numbers of social contacts than the general population, particularly if living in university halls of residence accommodation. Mathematical models are useful tools for understanding the potential spread of infection and are being actively used to inform policy about the management of COVID−19. Our aim was to provide a rapid review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
1
29
0
1
Order By: Relevance
“…These infections will have an unavoidable impact on hospitalisations and mortality, since a proportion of such cases are likely to result in severe infections [8] . The high rates of infection in young adults have implications for the spread of the virus in colleges and universities where local outbreaks are already being detected [9] .…”
Section: Discussionmentioning
confidence: 99%
“…These infections will have an unavoidable impact on hospitalisations and mortality, since a proportion of such cases are likely to result in severe infections [8] . The high rates of infection in young adults have implications for the spread of the virus in colleges and universities where local outbreaks are already being detected [9] .…”
Section: Discussionmentioning
confidence: 99%
“…In the midst of the COVID-19 pandemic, university students represent a demographic in the population who are likely to experience low rates of symptomatic infection 1 while being in a high contact social setting 2,3 . Extensive testing is required to monitor and manage potentially high rates of SARS-CoV-2 infection within a student population, particularly to minimise transmission to vulnerable individuals and groups, both within and outside of the student population 4 . Recent modelling work demonstrated that very frequent testing would be required to impact transmission 5 , which comes at a high cost.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of modelling analyses have already been carried out pertaining to transmission of SARS-CoV-2 within universities, and subsequent levels of COVID-19 disease [10]. These modelling studies have been predominately US-focused [11][12][13][14][15], potentially due to their earlier return.…”
Section: Introductionmentioning
confidence: 99%